A Companion to the Early Modern Cardinal
1 online resource.
Keywords: A Companion to the Early Modern Cardinal is the first comprehensive overview of its subject in English or any language. Cardinals are best known as the pope’s electors, but in the centuries from 1400 to 1800 they were so much more: pastors, inquisitors, diplomats, bureaucrats, statesmen, saints; entrepreneurs and investors; patrons of the arts, of music, literature, and science. Thirty-five essays explain their social background, positions and roles in Rome and beyond, and what they meant for wider society. This volume shows the impact which those men who took up the purple had in their respective fields and how their tenure of office shaped the entangled histories of Rome and the Catholic Church from a European and global perspective.